2022
DOI: 10.1080/10618600.2022.2116445
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Analysis of Locally Parameterized Shapes

Abstract: In statistical shape analysis, the establishment of correspondence and defining shape representation are crucial steps for hypothesis testing to detect and explain local dissimilarities between two groups of objects. Most commonly used shape representations are based on object properties that are either extrinsic or noninvariant to rigid transformation. Shape analysis based on noninvariant properties is biased because the act of alignment is necessary, and shape analysis based on extrinsic properties could be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…Following Pizer et al (2022) and Taheri and Schulz (2022), in this work, we consider an SO as a slab with a swept skeletal structure such that each cross-section is a 2D GC, the length of the spine (i.e., the SO's center curve) is notably larger than the length of the skeleton of each cross-section. The intersection of the spine with each 2D GC is a point on and (approximately) at the middle of the 2D GC's skeleton.…”
Section: Basic Terms and Definitionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Following Pizer et al (2022) and Taheri and Schulz (2022), in this work, we consider an SO as a slab with a swept skeletal structure such that each cross-section is a 2D GC, the length of the spine (i.e., the SO's center curve) is notably larger than the length of the skeleton of each cross-section. The intersection of the spine with each 2D GC is a point on and (approximately) at the middle of the 2D GC's skeleton.…”
Section: Basic Terms and Definitionsmentioning
confidence: 99%
“…The LP-dss-rep can be used for both shape analysis (i.e., after removing the size) or size-and-shape analysis (i.e., by preserving the size) (Dryden and Mardia, 2016). Since the LP-dss-rep is invariant to rigid transformation, for shape analysis we remove the scale by dividing the vectors' lengths by the size of the LP-dss-rep, which we call LP-size (Taheri and Schulz, 2022). The LP-size is the geometric mean of the vectors' length as…”
Section: Lp-dss-repmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, as presented in Section Statistics on S-reps for Single and Multiple Objects, Taheri and Schulz (2021) and Liu et al (2021b) have shown serious advantages to classification and hypothesis testing when discretized features according to the fitted frame were used in the statistics.…”
Section: Skeletal Models and S-reps: Definitions And Mathematicsmentioning
confidence: 99%
“…However, research so far has shown little advantage to the alternative method of Euclideanization in various classification applications, so our standard technique is sphere-by-sphere Euclideanization. Schulz et al (2015) and Taheri and Schulz (2021) have used these features to do hypothesis testing between s-rep classes, studying which geometric object properties (feature tuples capturing a single geometric property, such as a spoke direction) differ significantly between the classes. Taheri showed in experiments comparing hippocampi between typical humans and those with Parkinson's disease that the fitted-frame based features produce superior detections of differences than those using global coordinates.…”
Section: Single Object Applicationsmentioning
confidence: 99%